Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.17795/jhealthscope-15728
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nitrate Removal by Nano-Scaled Zero-Valent Iron Using Response Surface Methodology

Abstract: Background: Contamination of water resources with nitrate is a serious environmental problem in many regions of the world. In addition, this problem has been observed in some regions of Iran. As Nitrate is threatening for human health and environment, it must be decreased to standard levels in drinking water. Objectives: The purpose of this research was to model the nitrate removal from water by nano-scaled zero-valent iron (nZVI) using response surface methodology and to investigate the effects of the nZVI do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…This removal decrease may be because of the competitive adsorption among NO 3 − and interfering Cl − ions toward the adsorbent. Similar findings were reported by Kim and Zazouli in their works on nitrate adsorption by nZVI [22,64]. Ali et al [33] also reported the same result for atrazine herbicide adsorption onto the iron nanocomposite.…”
Section: Effect Of Ionic Strengthsupporting
confidence: 86%
“…This removal decrease may be because of the competitive adsorption among NO 3 − and interfering Cl − ions toward the adsorbent. Similar findings were reported by Kim and Zazouli in their works on nitrate adsorption by nZVI [22,64]. Ali et al [33] also reported the same result for atrazine herbicide adsorption onto the iron nanocomposite.…”
Section: Effect Of Ionic Strengthsupporting
confidence: 86%
“…Therefore by increasing the contact time and level of NZVI, nitrate removal rate increases as well. In other words, by increase of ionic strength and initial concentration, nitrate removal is reduced (18).…”
Section: )mentioning
confidence: 99%
“…Response surface methodology (RSM) is such one. RSM is an effective technique for analyzing the interactions among factors, exploring the relationships between the response and the independent variables, and optimizing the processes or products where multiple variables may influence the outputs (Wang et al 2010, Zazouli et al 2014, Fouladitajar et al 2014, Mourabet et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of RSM is the small number of experimental trials needed to evaluate multiple parameters and their interactions (Wang et al 2010, Zazouli et al 2014, Fouladitajar et al 2014, Boubakri et al 2014a, and this makes the optimization process more efficient and costeffective in terms of both manpower and resources.…”
Section: Introductionmentioning
confidence: 99%